The Role of Monocytes and Macrophages in Human Atherosclerosis, Plaque Neoangiogenesis, and Atherothrombosis - Francesco Moroni; Enrico Ammirati; Giuseppe Danilo Norata; Marco Magnoni; Paolo G. Camici (Hindawi Limited, 2019)
Atherosclerosis is one of the leading causes of death and disability worldwide. It is a complex disease characterized by lipid accumulation within the arterial wall, inflammation, local neoangiogenesis, and apoptosis. Innate immune effectors, in particular monocytes and macrophages, play a pivotal role in atherosclerosis initiation and progression. Although most of available evidence on the role of monocytes and macrophages in atherosclerosis is derived from animal studies, a growing body of evidence elucidating the role of these mononuclear cell subtypes in human atherosclerosis is currently accumulating. A novel pathogenic role of monocytes and macrophages in terms of atherosclerosis initiation and progression, in particular concerning the role of these cell subsets in neovascularization, has been discovered. The aim of the present article is to review currently available evidence on the role of monocytes and macrophages in human atherosclerosis and in relation to plaque characteristics, such as plaque neoangiogenesis, and patients' prognosis and their potential role as biomarkers.